The Impacts of COVID-19 on Women-Owned Enterprises in Ethiopia : Findings from a High-Frequency Phone Survey - Abebe, Girum (World Bank, Washington, DC, 2020)
This brief summarizes findings from a high-frequency survey of women-owned firms in Ethiopia which participate in the International Development Association (IDA) - financed Women Entrepreneurship Development Project (WEDP). Over the past five years, WEDP reached nearly 40,000 women-owned firms in Ethiopia with meso-loans and business training. Many WEDP firms had been on a high-growth trajectory, with firms that benefited from WEDP services growing incomes by 67 percent and employment by 55 percent over a three-year period prior to the crisis. This brief is based on the results from the first round of the survey, implemented between May 15, 2020 and June 15, 2020, revealing some initial insights into the scale of the impacts and the nature of the challenges currently facing the WEDP firms.